Los estilos gerenciales y su influencia en la gestión de empresas del sector de servicios de la ciudad de Trujillo - Recuenco Cabrera, Aurelio Daniel (2015)
This research work aimed to determine the managerial styles used by the service companies among the areas of finance, telecommunication and entertainment and their level of influence on management of themselves for being some areas very productives in recent years. To select the sample population was taken into account the criterion of representativeness in economic growth and a representative company of every area of the city was chosen to collect data. The surveys were applied to both the management staff and the subordinate staff and for which it was based on the classification described by Rensis Likert, known like “Management Systems”, considered one of the most reliable. Among the main factors studied were taken in mind: leadership, motivation, communication, decision, objectives and/or goals and control. This work is within the “Applied Research” and “Descriptive Research” fields and the research design is the “No Transaction Experimental One-Box”. The most important results are: a) the application of the advisory and participative styles being discarded the authoritarian styles; b) the predominance of the advisory style in almost all factors; c) the predominance of the advisory style on the managerial staff as on the subordinate staff; and d) the management is between good or optimal. All this led us to conclude that the managerial styles influence mainly on management of the service companies, observing a predominance of the advisory and participative styles.